Bahasa Arab Sebagai Simbol Identitas Religius: Sebuah Pendekatan Fenomenologis - Assakinah, Aqillah; Simanjuntak, Fattakhul Rizky Dinda; Azzura, Putri (EL-EMIR Institute, 2025)
This study explores in depth the role of Arabic language instruction in strengthening cultural identity and supporting Islamic education among students. The findings indicate that learning Arabic not only enhances understanding of Islamic teachings but also promotes greater social engagement and the preservation of local cultural values aligned with Islamic principles. Arabic is positioned as a crucial medium that bridges formal education with spiritual and historical cultural heritage. To ensure the validity and reliability of the data, this study employed methodological triangulation and pre-testing of research instruments. The analysis reveals that the applied approach successfully uncovered the strong relationship between Arabic language proficiency and the reinforcement of both Islamic and cultural identity among learners. These findings provide valuable insights into the integration of language and culture within education and offer a solid foundation for the implementation of similar programs in other Muslim communities.